Case Report: A rare case of pulmonary actinomycosis and concomitant small cell lung cancer - Fang, Shilin; Wang, Jianli; Zhu, Xiang; Gai, Xiaoyan; Sun, Yongchang (Frontiers in Medicine, 2025)
Pulmonary actinomycosis is a rare chronic granulomatous infection with non-specific clinical and imaging manifestations, often misdiagnosed as lung cancer. We present the case of an elderly male smoker with two pulmonary space-occupying lesions on the left and right sides, respectively, both showing hypermetabolism on positron emission tomography-computed tomography (PET/CT). The CT-guided lung biopsy of the left mass confirmed pulmonary actinomycosis. After treatment with penicillin for 1 month, the left lung mass got resolved significantly, while the right lung nodule increased during this period. Subsequently, the right nodule was diagnosed as small cell lung cancer via the endoscopic ultrasonography combined with LungPro navigation-guided transbronchoscopic lung biopsy and underwent thoracoscopic resection. The coexistence of pulmonary actinomycosis and lung cancer is extremely rare. This case underscores the importance of thorough diagnostic evaluation and careful differentiation between infectious and neoplastic pulmonary conditions to ensure appropriate management.